2022
DOI: 10.11591/ijece.v12i4.pp4099-4110
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer histological images nuclei segmentation and optimized classification with deep learning

Abstract: Breast cancer incidences have grown worldwide during the previous few years. The histological images obtained from a biopsy of breast tissues are regarded as being the highest accurate approach to determine whether any cells exhibit symptoms of cancer. The visible position of nuclei inside the image is achieved through the use of instance segmentation, nevertheless, this work involves nucleus segmentation and features classification of the predicted nucleus for the achievement of best accuracy. The extracted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Recent studies have demonstrated the effective application of convolution neural networks (CNNs) in segmenting medical images across various fields such as breast cancer [9], [10] and lung segmentation [11]. Precise segmentation of the LV region, particularly areas containing scar tissue, provides a robust foundation for precise subsequent segmentation of myocardial scar tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated the effective application of convolution neural networks (CNNs) in segmenting medical images across various fields such as breast cancer [9], [10] and lung segmentation [11]. Precise segmentation of the LV region, particularly areas containing scar tissue, provides a robust foundation for precise subsequent segmentation of myocardial scar tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer diagnosis and prediction has garnered a lot of attention in recent years, and numerous ways have been taken to address this issue [9]- [12]. The present focus is on machine learning and the semantic web.…”
Section: Introductionmentioning
confidence: 99%